Predicting factors of positive orientation and attitudes towards nursing: A quantitative cross-sectional study. (May 2016) - ten Hoeve, Yvonne; Castelein, Stynke; Jansen, Wiebren; Jansen, Gerard; Roodbol, Petrie
Abstract: Background: Previous studies have identified various reasons for students to choose a career in nursing. Students at the start of their programme hold a great variety of images and perceptions of nursing which can affect their orientation and attitudes towards their future profession. Objectives: This paper aims to examine nursing students' orientation and attitudes towards nursing at the beginning of their educational programme, and to explore predictors of positive orientation and attitudes. Design: The study used a quantitative cross-sectional design. Settings: A survey was conducted among first-year nursing students at four nursing universities of applied sciences in the Netherlands. Participants: Questionnaires were administered to all students enrolled in a bachelor of nursing programme (n = 1414) at these universities. Methods: Respondents completed a survey consisting of: 1) Nursing Orientation Tool, 2) Nursing Attitude Questionnaire, and 3) demographic data such as gender, living status, nursing experience, preliminary training, first-choice programme, and career choice. Kruskal Wallis tests, with post hoc Mann Whitney U tests, were used to compare group scores. Multiple regression was performed to investigate predictors of positive orientation and attitudes towards nursing. Results: Students in this study sample (n = 1244) strongly agreed with statements related to caring, nursing expertise, professional nursing knowledge and the application of this knowledge. Predictors of positive orientation and attitudes towards nursing include having nursing/caring experience, indicating nursing as the first choice for study, preliminary vocational training, and a desire to make a career in nursing. Conclusions: Data from this survey suggest a link between personal and environmental characteristics and motivations to select nursing as a career. Understanding which factors predict positive orientation and attitudes towards nursing could offer educators a tool in the recruitment and selection assessment of new students. Highlights: Nursing students start their programmes with quite favourable views of nursing. Personal and environmental characteristics predict students' perceptions of nursing. Mastering knowledge and its application are in line with the Bologna agreement. Predicting factors could offer a tool in the recruitment assessment of students.